The Fractured Self: Exploring Selfhood in the Neuronovel The Echo Maker and the Neuromemoir Brain on Fire - Bonnie Cross (European Journal of American Studies)
This paper will focus on two works: the neuronovel The Echo Maker (2006) by Richard Powers, a fictional account of Mark Schluter who suffers from Capgras Syndrome, that is, a rare neurological condition that results in the patient’s belief that their loved ones have been replaced with exact copies; and the neuromemoir Brain on Fire: My Month of Madness (2012) by Susannah Cahalan, which describes Cahalan’s experiences as she is diagnosed with anti-NMDA receptor encephalitis, a rare auto-immune disease. Both works have protagonists that suffer from a serious brain illness and must rely on their own perceptions, those of family and friends, and neuroscientific research in order to heal and create a more cohesive sense of self again. I argue that The Echo Maker and Brain on Fire complicate the perception of selfhood as the main character in each text can no longer trust their own perceptions and must instead weave together their fragmented personal experience, background from their social groups, and scientific explanations of their conditions to regain a sense of self. The narratives of The Echo Maker and Brain on Fire combine these different perspectives in an effort to regain a sense of selfhood that brain damage has fractured. While the result of the connections of millions of neurons is a smooth and linear perception of the self and the world around us, neuronarratives can complicate this process by revealing the divisions and occasional contradictions that occur in the combination.